DETERMINATION OF THE PUBESCENCE OF FOUR GENETIC MATERIALS OF BEAN (Phaseolus vulgaris L.) AND ITS EFFECT ON THE INSECT Bemisia tabaci (Gennadius) - PEÑA-ROJAS, EDUARDO A.; PANTOJA, ALBERTO; BEAVER, JAMES S. (Revista Colombiana de Entomología, 1992)
A study was conducted to describe the pubescence of four genotypes of common bean (Phaseolus vulgaris L.) and to study its effects on Bemisiatabaci (Gennadius). Genotypes under evaluation included fines A-429 and .DOR-303 and cultivars 27-R and PC-50. Nonglandular unciform and acerate trichomes were studied on the underside and top of the leaves of each genotype. The four genotypes showed variation in trichome size and density. In general, cultivars 27-R- and PC-50 showed larger acerate trichomes (ATU) and unciform trichomes (UTU) on the underside of the leaf. In the feeding and oviposition tests, it was shown that B. tabaci preferred the cultivar 27R. Cultivar PC-50 was the second prefered for B. tabaci. The number of adults and eggs of B. tabaci collected in fines A-429 and DOR303 indicated that the insect showed less preference for these fines. Results indicated that acerate and unciform trichomes in leaves of A-429, DOR- 303, 27-R and PC-50 were not an obstacle for B. tabaci to show a greater preference for 27-R and PC-50. The duration of the life cycle of B. tabaci was similar for all bean genotypes (an average of 30.8 days). The incubation period of eggs (7.6 days) and the duration of each of the four nymphal instars showed no differences in A-429, DOR-303, 27-R, and PC-50. Rather than pubescence, it appears that there are other characteristics that induce the preference of the insect for 27-R and PC-50. Results obtained suggest that A-429 and DOR-303 have or lack some Physico-chemical characteristics that make these lines fess attractive to the insect.